A novel framework for modelling the 3D mesostructure of steel fibre reinforced concrete. (1st July 2020) - Naderi, Sadjad; Zhang, Mingzhong
Graphical abstract: Highlights: Systematic distribution of fibres based on Delaunay criterion. Technique for modelling fibre with different profiles. Simulating particles based on relation of Voronoi and Delaunay structure. Modelling interfacial transition zone between aggregate and mortar. Perfect control on structural features in stochastic geometry. Abstract: This paper presents a novel method for modelling the three-dimensional four-phase mesostructure of steel fibre reinforced concrete (SFRC) consisting of coarse aggregates, mortar, interfacial transition zone and fibres, which provides several advanced features. It enables constructing various types of short discrete fibre like straight, spiral and hooked-end fibres with one- or three-dimensional elements while configuring their sizes and orientations. A key aspect of the approach is the capability of generating realistic-shaped aggregates with size- and shape-adjustability among fibres in a stochastic domain based on the relation of Voronoi and Delaunay structures. The mesostructure model is a powerful simulation tool for characterisation of such heterogenous materials because of the strong structural controllability, the algorithm's flexibility, the low computational cost and the productivity for many random samples in a statistical framework. To show the feasibility, the models were successfully implemented in a finite element case study to evaluate the elastic modulus of SFRC.